2013
DOI: 10.11144/javeriana.sc19-1.isco
|View full text |Cite
|
Sign up to set email alerts
|

Innermost stable circular orbits and epicyclic frequencies around a magnetized neutron star

Abstract: A full-relativistic approach is used to compute the radius of the innermost stable circular orbit (ISCO), the Keplerian, frame-dragging, precession and oscillation frequencies of the radial and vertical motions of neutral test particles orbiting the equatorial plane of a magnetized neutron star. The space-time around the star is modelled by the six parametric solution derived by Pachón et al. (2012) It is shown that the inclusion of an intense magnetic field, such as the one of a neutron star, have non-negligi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Kluźniak et al 1990;Shibata & Sasaki 1998;Pachón et al 2006Pachón et al , 2012Bakala et al 2012;Gutierrez et al 2013). It has been shown that for geodesic motion, these are well described by formulae derived considering NS spacetime approximated by the Hartle-Thorne metric (Hartle & Thorne 1968;Abramowicz et al 2003;Berti et al 2005).…”
Section: Behaviour Of Isco Radius and Ns Compactnessmentioning
confidence: 82%
“…Kluźniak et al 1990;Shibata & Sasaki 1998;Pachón et al 2006Pachón et al , 2012Bakala et al 2012;Gutierrez et al 2013). It has been shown that for geodesic motion, these are well described by formulae derived considering NS spacetime approximated by the Hartle-Thorne metric (Hartle & Thorne 1968;Abramowicz et al 2003;Berti et al 2005).…”
Section: Behaviour Of Isco Radius and Ns Compactnessmentioning
confidence: 82%
“…7 depicts the functional dependence on ζ, as in the case analyzed in Ref. [40], the Keplerian frequency increases with increasing ζ because the ISCO's radius decreases (see Fig. 6) as a consequence of the additional deformation of the space-time by the electromagnetic field.…”
Section: Influence Of the Electromagnetic Field In The Keplerian And mentioning
confidence: 84%
“…By combining the facts that (i) almost all the analytic closed form models for relevant astrophysical objects have been conceived in the frame of stationary axisymmetry geometry (see [40][41][42][43][44][45] for the case of neutron stars), (ii) powerful tools to construct exact solution to the Einstein-Maxwell field equation have been developed, e.g. [46][47][48], and (iii) systematic studies on the construction of exact solution from its physical content have been performed [49,50], a new analytic exact solution to the Einstein-Maxwell field equations is introduced below.…”
Section: Analytic Formulae Of the Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the conversion efficiency decreases due to the presence of the magnetic fields and of the tidal perturbations. Alternative studies of the effects of the neutron star's magnetic field on the exterior metric and the position of ISCO's can be found in [132,133].…”
Section: Discussion and Final Remarksmentioning
confidence: 99%